THE INFLUENCE OF TRUST, SATISFACTION AND MOTIVATION TOWARD CONSUMER LOYALTY (Case Study on Mobile Legend: Bang-Bang Player) - Tarigan, Michael Mitterand (International Humanities and Applied Science Journal, 2020)
The purpose of this research is to find out the â€œThe Influence of Trust, Satisfaction, and Motivation toward Consumer Loyalty (Case Study on Mobile Legend: Bang-Bang Player)â€. The population in this study is mobile gamer who plays Mobile Legend: Bang-Bang. The sample used in this study was collected in South Meruya, West Jakarta with the total of 130 respondents. The sampling technique used is purposive sampling by using a quantitative descriptive approach. Analysis of the data used is statistical analysis in the form of SEM-PLS. The results of this study indicate that Trust, Satisfaction, and Motivation have positive effect on Consumer Loyalty. Â Keywords: Trust, Satisfaction, Motivation, Consumer Loyalty, Mobile Legend: Bang-Bang.